Analisis Kualitas Pelayanan Publik Di Kantor Camat Hamparan Rawang Kota Sungai Penuh - Muhammad Farhan Fitra Reinaldy; Dwi Kurniawan; Ovie Yanti (CV. SINAR HOWUHOWU, 2026)
This research will discuss in more depth the analysis of the quality of public services at the Hamparan Rawang Subdistrict Office, Sungai Banyak City, Jambi Province. This research aims to analyze the quality of public services in Hamparan Rawang District, Sungai Banyak City, Jambi Province, to analyze the supporting and inhibiting factors of public services in Hamparan Rawang District, Sungai Full City, Jambi Province, and to analyze efforts to improve the quality of public services in the Hamparan Rawang District Head Office, Sungaiplain City. Full Jambi Province. This research uses a descriptive qualitative research method, which is research aimed at describing and describing events and phenomena that occur in the field and presenting data systematically, factually and accurately regarding facts or phenomena that occur in the field. The data collection techniques used in this research were interviews, observation and documentation. The theory that will be used in this research focuses on public services, elements of public services, principles of public services, principles of public services, and public service standards set at the Hamparan Rawang sub-district office.